2006
DOI: 10.1179/crn.2006.026
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Disclusion Time Reduction on Maximal Clench Muscle Activity Levels

Abstract: Simultaneous recording of excursive function and muscle activity on 62 MPDS patients demonstrated that reducing prolonged disclusion time (1.4 seconds per excursion) to short disclusion time (0.41 seconds per excursion) created a therapeutic effect such that within one month's time following treatment, there was an observed increase in the maximal clenching capacity of the masseter and temporalis muscles. This clinical treatment effect appears to be the result of decreased ischemia in these same muscles result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 13 publications
6
41
0
1
Order By: Relevance
“…The advent of disclusion time reduction therapy using properly performed ICAGD[16203233343536] is a potentially new direction in the treatment of myofascial pain dysfunction patients. Further studies with longer follow-up should be performed using ICAGD in the treatment of occluso-muscle pains of TMD disorders.…”
Section: Resultsmentioning
confidence: 99%
“…The advent of disclusion time reduction therapy using properly performed ICAGD[16203233343536] is a potentially new direction in the treatment of myofascial pain dysfunction patients. Further studies with longer follow-up should be performed using ICAGD in the treatment of occluso-muscle pains of TMD disorders.…”
Section: Resultsmentioning
confidence: 99%
“…The researchers [23,24] have observed the shorter disoccluding time is in the benefit of dental and joint structures. Extended disclusion time leads to increased EMG activityof masticatory muscles and stress on articular disc ligaments [25].…”
Section: Discussionmentioning
confidence: 99%
“…The disclusion time more than 1.39 s reported to initiate the elevated muscular contraction in masseter and temporalis. [1415] The EMG study showed the resting state muscular activity was observed in disclusion time <0.5 s. The prolonged disclusion time is also reported to be the etiological factor for myofunctional pain dysfunction syndrome. [15] Disclusion time during supine position was 0.872 (0.372), 0.862 (0.378), 1.051 (0.472) s for left lateral, right lateral and protrusive disclusion.…”
Section: Discussionmentioning
confidence: 99%